1961
DOI: 10.1139/m61-026
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Irradiation of Microorganisms in Relation to Food Preservation: I. The Comparative Sensitivities of Specific Bacteria of Public Health Significance

Abstract: The limits of tolerance to gamma irradiation have been determined for 21 cultures representative of the following bacterial species of public health significance in foods: Staphylococcus aureus, Escherichia coli (types I and II), Aerobacler aerogenes, A. cloacae, Streptococcus faecalis, Salmonella gallinarum, S. tennessee, Mycobacterium tuberculosis, Clostridium botulinum (types A and E). A several-fold difference in radiation sensitivity has been demonstrated, specific sensitivity being influenced by the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

1969
1969
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
0
10
2
Order By: Relevance
“…This appeared questionable as such results were not compatible with the results we obtained with S. aureus ATCC 13565. Further, Erdman et al (1961) and Tiwari and Maxcy (1972) reported D-values for S. aweus in broth that were significantly higher than those we obtained in MDCM. The resistance (D-value = 0.36 kGy) of stationary phase S. aureus ATCC 13565 to gamma radiation when mixed with MDCM was lower than most serovars of Salmonella reported by Thayer et al (1990).…”
Section: Challenge Studycontrasting
confidence: 86%
See 3 more Smart Citations
“…This appeared questionable as such results were not compatible with the results we obtained with S. aureus ATCC 13565. Further, Erdman et al (1961) and Tiwari and Maxcy (1972) reported D-values for S. aweus in broth that were significantly higher than those we obtained in MDCM. The resistance (D-value = 0.36 kGy) of stationary phase S. aureus ATCC 13565 to gamma radiation when mixed with MDCM was lower than most serovars of Salmonella reported by Thayer et al (1990).…”
Section: Challenge Studycontrasting
confidence: 86%
“…Enterotoxin was found only in the non-irradiated samples that were subjected to abuse for 20 hr at 35°C (Table 2). DISCUSSION ERDMAN et al (1961) reported that the strains of 5. uureu.s they examined had greater resistance to gamma radiation than did salmonellae. This appeared questionable as such results were not compatible with the results we obtained with S. aureus ATCC 13565.…”
Section: Effect Of Radiation Dose and Temperature Of Irradiationmentioning
confidence: 96%
See 2 more Smart Citations
“…The radiation inactivation of Clostridium botulinum toxin has been studied and has been found to be radioresistant. Erdman, Thatcher & MacQueen (1961) reported that there was no effect on the activity of type A toxin in pork sausage or broth at irradiation doses up to 2.2 x lo6 rep. Wagennaar & Dack (1960) noted that the inactivation dose for the toxin depended upon the substrate, cheese affording greater protection than did Trypticase broth or phosphate buffer. Type E toxin was also found to be radioresistant and Skulberg (1965) reported the decimal reduction dose (Dlo value) as 2.1 Mrad.…”
mentioning
confidence: 99%